1996
DOI: 10.1111/j.1432-1033.1996.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Structure of the Active Site of Monoamine Oxidase‐B by Affinity Labeling with the Selective Inhibitor Lazabemide and by Site‐Directed Mutagenesis

Abstract: The structural features of the active site of human monoamine oxidase El (MAO-B) were investigated by affinity labeling and site-directed mutagenesis. The pseudosubstrate inhibitor N-[2-aminoethyl1-5-chloro-2-pyridine carboxamide HCI (lazabemide) can be irreversibly linked to MAO-B by reduction of the enzyme-inhibitor complex with NaBH,CN. Analysis of the flavin spectrum of ['Hllazabemide-labeled human MAO-B indicated that insertion of the inhibitor did not occur into the isoalloxazine ring of FAD. After tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The labeled putative active-site tryptic peptides were isolated and found to contain the FAD-modified Cys-397. Substitution of His-382 of MAO B with an Arg greatly reduced the enzymatic activity, which suggests that this residue may represent a nucleophile relevant for MAO B catalytic activity (Cesura et al 1996). Cesura et al (1996) also demonstrated that a MAO B Thr-158 to Ala mutation resulted in a dramatic loss of enzymatic activity.…”
Section: Structural Requirements Of Mao a And B That Are Essential Fomentioning
confidence: 94%
See 2 more Smart Citations
“…The labeled putative active-site tryptic peptides were isolated and found to contain the FAD-modified Cys-397. Substitution of His-382 of MAO B with an Arg greatly reduced the enzymatic activity, which suggests that this residue may represent a nucleophile relevant for MAO B catalytic activity (Cesura et al 1996). Cesura et al (1996) also demonstrated that a MAO B Thr-158 to Ala mutation resulted in a dramatic loss of enzymatic activity.…”
Section: Structural Requirements Of Mao a And B That Are Essential Fomentioning
confidence: 94%
“…Substitution of His-382 of MAO B with an Arg greatly reduced the enzymatic activity, which suggests that this residue may represent a nucleophile relevant for MAO B catalytic activity (Cesura et al 1996). Cesura et al (1996) also demonstrated that a MAO B Thr-158 to Ala mutation resulted in a dramatic loss of enzymatic activity. This finding is consistent with the possible role of Cys-156 in MAO B. Interestingly, substitution of Cys-389 by Ala completely abolished the MAO B activity (Cesura et al 1996), and substitution of the same residue to Ser does not appear to change the enzymatic activity (Wu et al 1993).…”
Section: Structural Requirements Of Mao a And B That Are Essential Fomentioning
confidence: 94%
See 1 more Smart Citation
“…This compound belongs to a class of highly specific MAO-B inhibitors, which includes lazabemide. A previous study (4) suggested this inhibitor binds to a site on the enzyme other than the flavin moiety. Tranylcypromine (trans-2-phenylcyclopropylamine) has been known for Ͼ40 years as a MAO inhibitor and used clinically as an antidepressant.…”
mentioning
confidence: 88%
“…They are closely linked on the X chromosome (Lan et al, 1989) and have an identical intron-exon organization, indicating that they are derived from a common ancestral gene (Grimsby et al, 1991). Knocking out the MAO A gene resulted in aggressive behavior in mice (Cases et al, 1995), whereas knocking out the MAO B gene resulted in mice resistant to the parkinsonism-inducing toxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (Grimsby et al, 1997).To determine the region(s) responsible for the distinct substrate and inhibitor preferences of the two isoenzymes, we and other groups have made point mutants and chimeric MAO constructs exchanging corresponding portions of the isoenzymes (Gottowik et al, 1993(Gottowik et al, , 1995Wu et al, 1993;Tsugeno et al, 1995;Cesura et al, 1996;Chen et al, 1996). It has been shown that amino acid segments 161-375 in human MAO A and 152-366 in human MAO B contain part of the domain responsible for determining preference (Grimsby et al, 1996).…”
mentioning
confidence: 99%